2022
DOI: 10.3390/ijms23169006
|View full text |Cite
|
Sign up to set email alerts
|

Making the Rounds: Exploring the Role of Circulating Tumor DNA (ctDNA) in Non-Small Cell Lung Cancer

Abstract: Advancements in the clinical practice of non-small cell lung cancer (NSCLC) are shifting treatment paradigms towards increasingly personalized approaches. Liquid biopsies using various circulating analytes provide minimally invasive methods of sampling the molecular content within tumor cells. Plasma-derived circulating tumor DNA (ctDNA), the tumor-derived component of cell-free DNA (cfDNA), is the most extensively studied analyte and has a growing list of applications in the clinical management of NSCLC. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 129 publications
0
8
0
1
Order By: Relevance
“…Since our group and other researchers demonstrated that the detection and quantification of methylated ctDNA is a useful approach for therapy monitoring in lung cancer patients [ 14 , 15 , 16 ], more papers on this subject were published [ 20 , 21 ]. Moreover, the incorporation of liquid profiling as an additional clinical tool for the diagnosis, treatment stratification, detection of resistance mechanisms, and prognostic indication in lung cancer patients has been shown [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since our group and other researchers demonstrated that the detection and quantification of methylated ctDNA is a useful approach for therapy monitoring in lung cancer patients [ 14 , 15 , 16 ], more papers on this subject were published [ 20 , 21 ]. Moreover, the incorporation of liquid profiling as an additional clinical tool for the diagnosis, treatment stratification, detection of resistance mechanisms, and prognostic indication in lung cancer patients has been shown [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cancer progression will also affect the ctDNA/cfDNA ratio [45,72]. At the step of sample preparation, it is important to centrifuge blood as soon as possible after collection to lower the risk of DNA contamination caused by cell lysis [73]. Various protocols suggest proceeding with centrifugation at different temperatures and speed conditions, depending on laboratory equipment; however, in general, centrifugation for 10 min at 1000-2000× g using a refrigerated centrifuge allows obtaining high-quality plasma, while centrifugation for 15 min at 2000× g removes platelets from the plasma [74].…”
Section: Variant Allele Frequency (Vaf)mentioning
confidence: 99%
“…The predictive power of ccfDNA extends beyond cancer, holding promise in various other diseases where the monitoring of ccfDNA can aid in predicting disease flare-ups or relapse. This can be particularly valuable in managing chronic conditions, allowing for preemptive adjustments in treatment to mitigate the impact of a relapse or exacerbation [39].…”
Section: Predicting Disease Relapsementioning
confidence: 99%